Penerapan Metode Demonstrasi Terhadap Hasil Belajar Kognitif dan Psikomotor pada Pelatihan Pembuatan Donat Isi di Pondok Pesantren Nurul Amin Jember - Ridho Fibriansyah; Nugrahani Astuti; Lucia Tri Pangesthi; Ita Fatkhur Romadhoni (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This study used a pre-experimental design to study the effectiveness of a demonstration method in training female students at Nurul Amin Jember Islamic Boarding School. The research involved 128 female students and 30 female students, using observation, tests, and questionnaires. This research is a form of training by applying the compaction method to making filled donuts to find out: 1) instructor activities in applying the freezing method; 2) trainee activities in applying the freezing method; 3) cognitive and psychomotor learning outcomes in applying the freezing method; and 4) trainee responses in applying the freezing method. The research results show that instructor activities were in the very good category. The training participants' activities received a percentage score of 98% in the introduction, 92% in the core activities, and 100% in the closing. The participants' activities were included in the very good training category. In the pre-test, 5 training participants got a score of >70 with a percentage of 7%, and for the pre-test, there were 30 training participants who got >70 with a percentage of 100%. The scores obtained from pre-test to post-test increased by 83%. For psychomotor results, the highest score was 98 and the lowest was 93, with a very good category score. The training participants' response to the exposure method obtained a percentage score of 100% in the very good category. So it can be concluded that the application of the compression method can improve learning outcomes and have a good impact if used for training